2021
DOI: 10.1001/jamacardio.2021.0487
|View full text |Cite
|
Sign up to set email alerts
|

Association of Socioeconomic Disadvantage With Long-term Mortality After Myocardial Infarction

Abstract: IMPORTANCE Socioeconomic disadvantage is associated with poor health outcomes. However, whether socioeconomic factors are associated with post-myocardial infarction (MI) outcomes in younger patient populations is unknown.OBJECTIVE To evaluate the association of neighborhood-level socioeconomic disadvantage with long-term outcomes among patients who experienced an MI at a young age. DESIGN, SETTING, AND PARTICIPANTSThis cohort study analyzed patients in the Mass General Brigham YOUNG-MI Registry (at Brigham and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 50 publications
1
25
0
1
Order By: Relevance
“…In our study, socioeconomic deprivation was not a significant barrier to listing for HT, as ADI and SES index were not found to be significant predictors after multivariate adjustment. This analysis utilized two metrics of socioeconomic deprivation, the ADI and SES index that have been previously demonstrated to be associated with poor cardiovascular health outcomes and incident heart failure risk 9–11 . A previous analysis of patients in UNOS bridged to transplant with LVAD found that patients had similar freedom from death or delisting on LVAD support independent of SES.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, socioeconomic deprivation was not a significant barrier to listing for HT, as ADI and SES index were not found to be significant predictors after multivariate adjustment. This analysis utilized two metrics of socioeconomic deprivation, the ADI and SES index that have been previously demonstrated to be associated with poor cardiovascular health outcomes and incident heart failure risk 9–11 . A previous analysis of patients in UNOS bridged to transplant with LVAD found that patients had similar freedom from death or delisting on LVAD support independent of SES.…”
Section: Discussionmentioning
confidence: 99%
“… 10 The association of lower SEP with higher mortality after myocardial infarction, both in the short term and long term, has been extensively confirmed. 2 , 3 , 4 , 7 , 9 , 20 Despite decades of literature establishing this relationship, Davis et al previously showed that “there are no studies describing attempts to improve acute coronary heart disease” as it relates to cardiovascular health disparities. 21…”
Section: Discussionmentioning
confidence: 99%
“…В настоящем исследовании среди участников выраженной дифференциации по месту проживания в городской и сельской местности не получено. Регистровый анализ Brigham YOUNG-MI у пациентов с ИМ показал, что не столько само отношение места проживания к селу или городу, а именно социально-экономическое, этническое и религиозное благополучие района проживания являются детерминирующими факторами сердечно-сосудистого риска [18].…”
Section: материал и методыunclassified